Pelatihan Pembuatan Travelling Bag sebagai Rekrutmen Sumber Daya Manusia dan Pemberdayaan Perempuan - Anggun Fajar Ramadhani; Arfatul Makiyah; Nurni Arrina Lestari (Penerbit Goodwood, 2026)
Purpose: This community service activity aims to provide training traveling bags to women in the local community as part of human resource recruitment and economic empowerment efforts. Methodology/approach: Through this training, participants are expected to develop practical skills relevant to the creative industry, particularly in bag production. The program is also designed to increase women's economic independence by opening up new job The stages carried out in the Implementation of the traveling bag making training program are: Identification and Selection of Participants, Development of Curriculum and Training Modules, Technical Training in Traveling Bag Making, Technical Assistance and Guidance, Business Management and Marketing Training, and Evaluation and Monitoring. Results/findings: The results of this activity showed a 50% increase in bag-making skills, significant improvements in participants' technical abilities, and increased entrepreneurial motivation. This training not only provided new skills but also contributed to strengthening the local economy by creating community-based business opportunities. Conclusions: Based on the introduction, activity implementation recruitment training to produce travel bag from knitted materials in Cipanengah Village was implemented well and smoothly, improving the skills of the participants. Limitations: Student response data were not taken, even though it was necessary to confirm the results of community responses to begin business opportunities. Contributions: Improve community ability to design in bag production materials, improve community’ understanding of concepts, and shape community' character values and sustainability.